Three-dimensional porous material, negative electrode composite material and application
By designing three-dimensional porous materials with open opening diameter distribution concentrated in the range of ≤2nm, the problem of uneven deposition of electrode materials in the prior art is solved, more efficient deposition and structural uniformity are achieved, and the circulation performance and life of the battery are significantly improved.
Patent Information
- Application Number
- CN202311282907.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-27
- Publication Date
- 2025-03-28
AI Technical Summary
The pore sizes of existing three-dimensional porous materials are widely distributed, resulting in uneven deposition of high-performance electrode materials, affecting battery performance and cycle life.
A three-dimensional porous material is designed, with the opening diameter distribution of the openings in the range of ≤2nm, the volume of micropores accounts for ≥70%, and the volume of the first type of pores accounts for ≥50%, so as to achieve more efficient deposition and structural uniformity.
Through this design, the adsorption and deposition efficiency of the active material and the concentration of particle size are significantly improved, the volume expansion and mechanical stress uneven problems of the battery during charging and discharging are reduced, and the cycle life of the battery is extended.
Smart Images

Figure CN119725421A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of battery technology, and in particular to three-dimensional porous materials, negative electrode composite materials and applications. Background Art
[0002] At present, the industry mostly uses carbon materials (e.g., graphite) as negative electrode materials for secondary batteries, but the specific capacity of carbon materials is relatively low, which seriously restricts the energy density of secondary batteries. In order to cater to the market's pursuit of high-energy-density batteries, high-performance electrode materials with high specific capacity (e.g., silicon negative electrode materials, etc.) have gradually attracted attention. However, the volume change rate of such high-performance electrode materials before and after the extraction / embedding of active ions is usually very large, which seriously affects the performance of the battery and shortens the cycle life of the battery.
[0003] To solve the above problems, the industry often deposits the above high-performance electrode materials in three-dimensional porous materials to limit their expansion. However, the existing three-dimensional porous materials have a wide pore size distribution, which is not conducive to the deposition of high-performance electrode materials, and will lead to poor structural uniformity of the final negative electrode material, which is still not conducive to the performance of battery performance. Summary of the invention
[0004] In view of this, the embodiments of the present application provide a three-dimensional porous material, a negative electrode composite material and an application. The three-dimensional porous material has a specially designed opening diameter distribution of the openings, a high proportion of effective deposition holes, and a high concentration of the opening diameter distribution of the openings, thereby achieving a better threshold limiting effect on the deposited material, and can be used to provide a negative electrode material with both high gram capacity and high structural stability.
[0005] A first aspect of an embodiment of the present application provides a three-dimensional porous material, comprising a plurality of openings. Based on the total opening volume of the three-dimensional porous material, the volume of openings with an opening diameter ≤2 nm accounts for ≥70%, and the volume of openings with an opening diameter in the range of 1 nm-2 nm accounts for ≥50%.
[0006] The opening diameter distribution concentration of the openings with an opening diameter ≤ 2nm in the above three-dimensional porous material is relatively high, and the volume proportion of the openings with an opening diameter in the range of 1nm-2nm is ≥50%, so that the opening diameter distribution of the three-dimensional porous material is relatively narrow and the effective deposition pore proportion is large, which can improve the adsorption deposition efficiency of active material particles (particles that can be used to form positive electrode active materials or negative electrode active materials, such as silane, etc.) in the three-dimensional porous material and the deposition utilization rate of the openings, and has a good limiting effect on the particle size of the deposited active material, which is conducive to the formation of extremely small nanoparticles. At the same time, the above three-dimensional porous material has good uniformity, so that the concentration and uniformity of the particle size of the deposited active material can be improved. Therefore, when the deposited material is a silicon-containing material, a phosphorus-containing material, etc., it can further alleviate its volume expansion during the battery charge and discharge cycle, and the problem of uneven distribution of mechanical stress caused by its volume expansion.
[0007] In some embodiments of the present application, based on the total open pore volume of the three-dimensional porous material, the volume of open pores with an opening diameter of ≤2 nm accounts for ≥85%. In this way, the uniformity of the three-dimensional porous material can be further improved, and when the active material is deposited in the three-dimensional porous material, the average particle size of the deposited active material can be further limited.
[0008] In some embodiments of the present application, based on the total open pore volume of the three-dimensional porous material, the volume proportion of the open pores with an opening diameter <1nm is ≤40%. In this way, it can be ensured that the proportion of effective deposition in the three-dimensional porous material is high. In some specific embodiments, based on the total open pore volume of the three-dimensional porous material, the volume proportion of the open pores with an opening diameter <1nm is ≤38%. In this way, when depositing active materials in the three-dimensional porous material, the mass proportion of the deposited active materials in the final composite material can be increased.
[0009] In some embodiments of the present application, the volume proportion of the pores with an opening diameter of >5 nm is <1%. When depositing active materials in a three-dimensional porous material, the average particle size of the deposited active materials can be further limited.
[0010] In some embodiments of the present application, the total pore volume of the three-dimensional porous material is greater than 0.5 cm 3 / g. In the case of the distribution of opening diameters of three-dimensional porous materials, the total pore volume is controlled to be >0.5cm 3 / g can make the number of effective deposition holes in the three-dimensional porous material more appropriate, thereby being used to provide a composite material with better comprehensive performance.
[0011] In some embodiments of the present application, the material of the three-dimensional porous material includes at least one of conductive carbon, conductive ceramic or metal.
[0012] The second aspect of an embodiment of the present application provides a negative electrode composite material, comprising the three-dimensional porous material provided in the first aspect of the present application and a plurality of nanoparticles located in the openings; the material of the nanoparticles comprises at least one of a silicon-containing material, a phosphorus-containing material or a tin-containing material.
[0013] Based on the special structural design of three-dimensional porous materials, the average particle size of nanoparticles is small, which can effectively reduce the expansion rate of the negative electrode composite material during the charge and discharge cycle; at the same time, the concentration of multiple nanoparticles in the negative electrode composite material is high within a small particle size range (the uniformity of the negative electrode composite material is good), so it can improve the uniformity of the internal mechanical stress distribution of the negative electrode composite material during the battery cycle, reduce the risk of rupture of the negative electrode composite material, and thus improve the battery cycle performance. In addition, based on the inherent properties of silicon-containing materials, phosphorus-containing materials, and tin-containing materials, the above-mentioned negative electrode composite material has a high reversible capacity.
[0014] In some embodiments of the present application, the size of the nanoparticles in at least one direction is ≤ 2 nm, which is more conducive to suppressing the volume change of the negative electrode composite material during the battery cycle.
[0015] In some embodiments of the present application, the negative electrode composite material further includes a coating layer coated on the surface of the three-dimensional porous material; the coating layer includes a carbon coating layer and / or a fast ion conductor coating layer, or a composite coating layer; wherein the composite coating layer includes a carbon material and a fast ion conductor material; the thickness of the coating layer is ≤20nm. The carbon coating layer can improve the electronic conductivity of the negative electrode composite material, and the fast ion conductor coating layer can improve the ionic conductivity of the negative electrode composite material, thereby both improving the rate performance of the battery; the composite coating layer can simultaneously improve the electronic conductivity and ionic conductivity of the negative electrode composite material. In addition, the above-mentioned coating layer can also serve as a physical isolation, effectively reducing the risk of silicon-containing materials, phosphorus-containing materials, and tin-containing materials being exposed to the surface of the negative electrode composite material, thereby improving the interface stability of the negative electrode composite material and being more conducive to the performance of the battery.
[0016] In some embodiments of the present application, the carbon coating layer is also formed in the openings, so as to further improve the electronic conductivity of the negative electrode composite material.
[0017] In some embodiments of the present application, the negative electrode composite material contains a doping element, and the doping element is at least one of N, P or S. Doping the negative electrode composite material can improve the electronic conductivity and stability of the negative electrode composite material.
[0018] In some embodiments of the present application, the nanoparticles contain the doping element, which is beneficial to improving the electronic conductivity and stability of the negative electrode composite material.
[0019] In some embodiments of the present application, the three-dimensional porous material contains the doping element. This is beneficial to improving the electronic conductivity of the negative electrode composite material. In some specific embodiments of the present application, the three-dimensional porous material and the nanoparticles contain the doping element at the same time. This can further improve the comprehensive performance of the negative electrode composite material.
[0020] In some embodiments of the present application, the mass proportion of the doping element in the negative electrode composite material is less than 10%. In this way, both the electronic conductivity and the reversible capacity of the negative electrode composite material can be taken into account.
[0021] In some embodiments of the present application, the mass of the plurality of nanoparticles accounts for 30%-80% of the total mass of the negative electrode composite material.
[0022] The third aspect of the embodiment of the present application provides a negative electrode plate, including a current collector and a negative electrode material layer arranged on the surface of the current collector, wherein the negative electrode material layer includes the negative electrode composite material provided in the second aspect of the embodiment of the present application. Due to the use of the negative electrode composite material provided in the embodiment of the present application, the negative electrode plate has a low volume expansion rate after battery cycling and can provide a higher reversible capacity, thereby being used to provide a secondary battery with both higher energy density and better cycle performance. The negative electrode plate can be a negative electrode plate used in a lithium secondary battery, or a negative electrode plate used in a sodium secondary battery.
[0023] The fourth aspect of the embodiment of the present application provides a secondary battery, including a negative electrode plate, a positive electrode plate, and an electrolyte located between the positive electrode plate and the negative electrode plate. Due to the use of the negative electrode plate provided by the third aspect of the embodiment of the present application, the secondary battery can have both high energy density and better cycle performance. The secondary battery can be a lithium secondary battery or a sodium secondary battery.
[0024] In some embodiments of the present application, the secondary battery is a liquid battery.
[0025] In some embodiments of the present application, the secondary battery is a solid-state battery.
[0026] The fifth aspect of the embodiment of the present application provides an electric device, including the secondary battery provided by the fourth aspect of the embodiment of the present application. In some embodiments of the present application, the above-mentioned electric device includes but is not limited to 3C electronic products, such as mobile phones, laptops, tablet computers, drones, wearable electronic devices, etc. In other embodiments of the present application, the above-mentioned electric device includes a power vehicle, such as a new energy vehicle, an electric bicycle, etc.
[0027] The sixth aspect of the embodiment of the present application provides an energy storage system, including the secondary battery provided by the fourth aspect of the embodiment of the present application. Due to the use of the secondary battery provided by the embodiment of the present application, the energy storage system can have a higher energy density.
[0028] In some implementations of the present application, the energy storage system includes an electrically connected energy storage device and a power converter, and the energy storage device includes a receiving cavity and the secondary battery received in the receiving cavity. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 A schematic diagram of the cross-section structure of a three-dimensional porous material provided in one embodiment of the present application;
[0030] Figure 2 A schematic diagram of the cross-section structure of a negative electrode composite material provided in one embodiment of the present application;
[0031] Figure 3A A schematic structural diagram of a cross section of a negative electrode composite material provided in another embodiment of the present application;
[0032] Figure 3B A schematic structural diagram of a cross section of a negative electrode composite material provided in yet another embodiment of the present application;
[0033] Figure 4 X-ray diffraction (XRD) spectra of the negative electrode composite material SC1 provided in the embodiment of the present application and the negative electrode composite material DSC2 of the comparative example;
[0034] Figure 5 A scanning electron microscope (SEM) photograph of the negative electrode composite material SC1 provided in the embodiment of the present application and a corresponding silicon element distribution diagram measured by an energy dispersive spectrometer (EDS);
[0035] Figure 6 The SEM photo of the comparative negative electrode composite material DSC2 and the corresponding EDS silicon element distribution map;
[0036] Figure 7 This is a transmission electron microscope (TEM) photograph of the negative electrode composite material SC1 provided in an embodiment of the present application.
[0037] Explanation of the accompanying figures: 1-three-dimensional porous material; 10-micropores; 11-first type of pores; 12-second type of pores; 20-third type of pores; 100-negative electrode composite material; 30-nanoparticles; 40-coating layer. DETAILED DESCRIPTION
[0038] With the innovation and replacement of electronic products, the market demand for battery energy density is getting higher and higher. The development of high-performance negative electrode materials such as silicon-based negative electrode materials, phosphorus-containing negative electrode materials and tin-based negative electrode materials has become one of the key technical routes. The volume change rate of the above-mentioned high-performance electrode materials before and after the extraction / insertion of active ions is extremely large. Taking lithium-ion batteries with silicon-based negative electrodes as an example, the volume expansion rate of silicon particles during the extraction and insertion of lithium is as high as 300%, which can easily lead to the rupture of negative electrode material particles, aggravate battery side reactions (for example, the thickening of the solid electrolyte interface film), and cause irreversible loss of active ions; even lead to cracking of the negative electrode plate, and the separation of the negative electrode material layer and the current collector, which seriously affects the battery cycle performance.
[0039] Taking silicon negative electrode materials as an example, in order to suppress the expansion of silicon negative electrode materials during battery cycling, the industry often deposits silicon-containing active materials (for example, silicon element) in the openings of three-dimensional porous materials, and generally adopts a vapor deposition process for preparation, specifically including: placing the three-dimensional porous material in silane gas, silane adsorbed in its openings and deposited into silicon particles, and obtaining a composite negative electrode material. However, the pore size distribution of the three-dimensional porous material in the prior art is wide, which not only affects the adsorption and deposition of silane by the openings, but also the particle size distribution of the silicon particles in the composite negative electrode material finally obtained is also relatively wide, which will lead to a large difference in the volume expansion effect of a large number of silicon particles with large particle size differences during the battery cycling process, so that the three-dimensional porous material has limited inhibitory effect on the expansion of silicon particles, and causes uneven distribution of mechanical stress of the composite negative electrode material particles, and the risk of rupture of the composite negative electrode material particles during the charge and discharge cycle is still high, affecting the battery cycle performance. However, the growth of silicon particles in the composite negative electrode material and the final particle size distribution are obviously affected by the pore size distribution of the three-dimensional porous material. Therefore, providing a three-dimensional porous material with a special pore size distribution design is one of the keys to overcoming the above technical problems.
[0040] In view of this, for the convenience of description, the following text will refer to pores with an opening diameter of ≤2nm as "micropores", pores with an opening diameter in the range of 1nm-2nm as "first-class pores", and pores with an opening diameter <1nm as "second-class pores", that is, micropores include first-class pores and second-class pores; pores with an opening diameter >5nm are collectively referred to as "third-class pores". Please refer to Figure 1 The embodiment of the present application provides a three-dimensional porous material 1. Based on the total open pore volume of the three-dimensional porous material 1, the volume proportion of open pores (micropores 10) with an opening diameter ≤2nm is ≥70%, and the volume proportion of open pores with an opening diameter in the range of 1nm-2nm (first type of pores 11) is ≥50%.
[0041] In the embodiment of the present application, the opening diameter and the distribution of the opening diameter in the three-dimensional porous material 1 are measured by gas adsorption and desorption test. Based on the principle of gas adsorption and desorption test (closed pores cannot be measured), the opening diameter of each opening measured refers specifically to the opening diameter measured by the gas adsorption and desorption test, which can be considered as the "maximum lateral dimension of the opening of the opening". Specifically, the shape of the micropores 10 can be spherical, quasi-spherical, long strip, irregular, etc. Among them, the gas used in the above-mentioned gas adsorption and desorption test can be but is not limited to nitrogen, carbon dioxide, argon, etc.
[0042] Specifically, the three-dimensional porous material 1 is placed in a gas adsorption-desorption tester, such as a nitrogen adsorption-desorption test. During the test, the degassing time is maintained at ≥30 min and the degassing temperature is maintained at ≥100°C to obtain the adsorption-desorption curve of the three-dimensional porous material 1, thereby obtaining the opening diameter distribution of the three-dimensional porous material 1.
[0043] In some specific embodiments of the present application, a small number of closed pores (pores into which gas cannot enter, not shown in the figure) may exist in the three-dimensional porous material 1. It should be noted that in the embodiments of the present application, the volume of the closed pores is not included in the total open pore volume of the above-mentioned three-dimensional porous material 1.
[0044] Understandably, the distribution of openings in three-dimensional porous materials is intricate. Generally, solid materials are prepared in their openings by deposition, and the above deposition includes but is not limited to chemical vapor deposition, sputtering deposition, etc. For porous materials, there are differences in the adsorption capacity of openings with different opening diameters for particles (e.g., gas molecules, atoms, ions, etc.): under the superposition effect of the interaction potential energy between the pore walls, the openings with an opening diameter ≤ 2nm have a stronger adsorption capacity for particles, and their threshold limiting effect is better, which is more conducive to limiting the particle size of the deposited material in the opening, and is more conducive to limiting the particle size distribution of the deposited material. More importantly, the inventors have found that the openings with an opening diameter in the range of 1nm-2nm have a stronger adsorption capacity for active material particles (particles that can be used to form positive active materials or negative active materials, such as silane, etc.) than openings with other opening diameters, and have a better threshold limiting effect on deposited materials. The opening diameter distribution of the openings in the three-dimensional porous material 1 provided in the embodiment of the present application is concentrated in the range of ≤2nm, and the sum of the volume percentages of the first type of pores 11 (that is, the opening diameter is 1nm-2nm) is ≥50%, the opening diameter distribution is narrow and the effective deposition pores account for a large proportion (the openings that can effectively adsorb particles and deposit them to form deposited materials account for a large proportion), so the adsorption and deposition efficiency of active material particles in the three-dimensional porous material 1 and the deposition utilization rate of the openings can be improved, so that the composite material can achieve a higher active material deposition load. In particular, when the deposited material is a high-performance electrode material, the gram capacity of the composite material finally obtained can be improved. At the same time, the uniformity of the above-mentioned three-dimensional porous material 1 is good, so that the concentration of the particle size of the active material finally deposited in its openings can be improved; and the above-mentioned three-dimensional porous material 1 has a good limiting effect on the particle size of the active material generated by deposition, which is conducive to the formation of extremely small nanoparticles. In the embodiment of the present application, extremely small nanoparticles refer to "nanoparticles with a size of at least one dimension ≤2nm". Therefore, when the deposited active material is a high-performance electrode material such as a silicon-containing material, a phosphorus-containing material, or a tin-containing material, the three-dimensional porous material 1 can better inhibit its volume expansion during the charge and discharge cycle, and improve the problem of uneven distribution of mechanical stress inside the three-dimensional porous material 1 and rupture caused by its volume expansion.
[0045] In the embodiment of the present application, based on the total open pore volume of the three-dimensional porous material 1, the volume proportion of the plurality of micropores 10 may be, but is not limited to, 70%, 75%, 80%, 85%, 88%, 90%, 92%, 95%, 98%, 99%, 100%, etc. If the volume proportion of the micropores 10 is too low, the volume proportion of the openings with an opening diameter of >2nm will increase, which is not conducive to the subsequent adsorption and deposition of other materials, nor is it conducive to the particle size control of the active material. When the deposited active material is the aforementioned high-performance electrode material such as the silicon-containing material, the effect on its volume expansion during the charge and discharge cycle is still limited.
[0046] In the embodiment of the present application, based on the total open pore volume of the three-dimensional porous material 1, the volume proportion of the plurality of first-type pores 11 may be, but is not limited to, 50%, 52%, 55%, 58%, 60%, 62%, 65%, 68%, 70%, 72%, 75%, 80%, 85%, 90%, 95%, etc. If the volume proportion of the micropores 10 is ≥ 70%, but the volume proportion of the first-type pores 11 is too low, it will make it difficult to achieve effective deposition of a large number of subsequent open pores. When the deposited active material is the aforementioned high-performance electrode material such as the silicon-containing material, the specific capacity of the composite material finally obtained will be too low.
[0047] In some embodiments of the present application, the volume proportion of the plurality of micropores 10 is ≥85% based on the total open pore volume of the three-dimensional porous material 1. In some specific embodiments, the volume proportion of the plurality of micropores 10 is ≥87%, for example, 87%-92%. The volume proportion of the micropores 10 in the three-dimensional porous material 1 is further increased, the volume proportion of the open pores with an opening diameter of >2nm is reduced, and the uniformity of the three-dimensional porous material 1 is better, thereby increasing the probability that the deposited active material is a very small nanoparticle. When the deposited active material is a high-performance electrode material such as a silicon-containing material, the volume expansion rate of the final composite material during the battery cycle can be further reduced, thereby reducing the problem of uneven distribution of mechanical stress inside the final composite material, and further reducing the risk of composite material rupture.
[0048] In some embodiments of the present application, based on the total open pore volume of the three-dimensional porous material 1, the volume proportion of the plurality of second-class pores 12 is ≤40%. It is difficult for the open pores with an opening diameter <1 nm to adsorb particles (for example, silane gas molecules). When the proportion of micropores 10 is high, controlling the volume proportion of the second-class pores 12 to ≤40% can increase the proportion of effective deposition pores, which is conducive to increasing the mass proportion of the deposited active material in the final composite material. In addition, when the second-class pores 12 exist in the three-dimensional porous material 1, the probability of the second-class pores 12 existing as "empty pores" in the final composite material is high, or in other words, because the adsorption is difficult, the particle size of the active material deposited in the final second-class pores 12 is very small and few, and the second-class pores 12 remain to form "empty pores", so when the deposited active material is the aforementioned high-performance negative electrode material such as silicon-containing material, the second-class pores 12 can be used as a buffer space for the expansion of high-performance electrode materials in other openings, so the overall expansion rate of the composite material can be reduced. Specifically, the volume proportion of the plurality of second type holes 12 may be 40%, 38%, 36%, 35%, 32%, 30%, 25%, 22%, 20%, 15%, 10%, 5%, 1%, etc.
[0049] In some embodiments of the present application, based on the total open pore volume of the three-dimensional porous material 1, the volume proportion of the plurality of second-type pores 12 is ≤ 38%. For example, 34%-38%. In this way, a certain expansion buffer space can be reserved inside the final composite material, while further increasing the mass proportion of the deposited material in the composite material.
[0050] In some embodiments of the present application, based on the total open pore volume of the three-dimensional porous material 1, the volume proportion of multiple third-type pores 20 is <1% (the volume proportion of pores with an opening diameter > 5nm is <1%). During the preparation process of the three-dimensional porous material 1, third-type pores 20 with an opening diameter > 5nm may be formed, which have a slightly weaker ability to adsorb particles than the micropores 10, and a slightly weaker effect on the particle size restriction of the deposited negative active material. By controlling the volume proportion of the third-type pores 20 to <1%, the probability of the appearance of active materials with larger particle sizes in the final composite material can be reduced, thereby further enhancing the threshold limiting effect of the three-dimensional porous material 1 on the deposited material. When the deposited material is the aforementioned high-performance electrode material such as a silicon-containing material, the expansion rate of the composite material during the charge and discharge cycle can be further reduced, and the problem of uneven distribution of its internal mechanical stress can be further improved. Specifically, the volume proportion of multiple third-type pores 20 is ≤0.7%, for example, 0.5%-0.7%.
[0051] In some embodiments of the present application, the total pore volume of the three-dimensional porous material 1 is greater than 0.5 cm 3 In the embodiment of the present application, the volume proportion of the micropores 10 and the first type of pores 11 of the three-dimensional porous material 1 is defined, and the total pore volume is controlled to be greater than 0.5 cm 3 / g can make the number of effective deposition pores in the three-dimensional porous material 1 more appropriate, so as to provide a composite material with better comprehensive performance. Specifically, the total pore volume of the three-dimensional porous material 1 can be but is not limited to 0.55cm 3 / g, 0.60cm 3 / g, 0.65cm 3 / g, 0.70cm 3 / g, 0.75cm 3 / g, 0.80cm 3 / g, 0.85cm 3 / g, 0.90cm 3 / g, etc. Further, the total pore volume of the three-dimensional porous material 1 is greater than 0.80 cm 3 / g, for example, 0.80cm 3 / g-0.90cm 3 In the present embodiment, the total pore volume of the three-dimensional porous material 1 is measured by a gas adsorption-desorption test.
[0052] In some embodiments of the present application, the D50 of the three-dimensional porous material 1 is in the range of 2μm-15μm. In some specific embodiments, the D50 of the three-dimensional porous material 1 is in the range of 7μm-8μm. Specifically, the D50 of the three-dimensional porous material 1 can be, but is not limited to, 2μm, 3μm, 4μm, 5μm, 6μm, 7μm, 8μm, 9μm, 10μm, 11μm, 12μm, 13μm, 14μm, 15μm, etc. When the three-dimensional porous material 1 is used to provide a negative electrode composite material, when the D50 of the negative electrode composite material is within the above range, the length of the deintercalation path of the active ions can be controlled within a reasonable range, which is conducive to the electrochemical performance of the battery. In the embodiment of the present application, the above D50 refers to the particle size corresponding to the cumulative particle size distribution percentage of the three-dimensional porous material 1 reaches 50%, and the D50 of the three-dimensional porous material 1 is tested using a laser particle size analyzer.
[0053] In some embodiments of the present application, the material of the three-dimensional porous material 1 includes at least one of conductive carbon, conductive ceramic or metal. Those skilled in the art can select according to application requirements.
[0054] In some embodiments of the present application, the material of the three-dimensional porous material 1 is conductive carbon. In some specific embodiments, the material of the three-dimensional porous material 1 is amorphous carbon. At this time, the true density of the three-dimensional porous material 1 is in the range of 1.0g / cc-2.3g / cc. In the embodiment of the present application, the true density of the three-dimensional porous material 1 is tested by the gas volume method. In addition, in some cases, there are closed pores in the three-dimensional porous material 1. At this time, limiting its true density also limits the volume proportion of the closed pores in the three-dimensional porous material 1 to a certain extent within a suitable range. Specifically, the true density of the three-dimensional porous material 1 can be, but is not limited to, 1.0g / cc, 1.2g / cc, 1.5g / cc, 1.8g / cc, 2.0g / cc, 2.1g / cc, 2.2g / cc, 2.3g / cc, etc.
[0055] In some embodiments of the present application, the material of the three-dimensional porous material 1 is conductive carbon, and further, the material of the three-dimensional porous material 1 is amorphous carbon; considering the preparation process of the three-dimensional porous material 1 and its preparation raw materials, the three-dimensional porous material 1 (that is, conductive carbon) also includes some heteroatoms, such as oxygen, hydrogen, nitrogen, sulfur, etc. The carbon content of the three-dimensional porous material 1 is >90wt.%. Specifically, the carbon content of the three-dimensional porous material 1 can be, but is not limited to, 91wt.%, 92wt.%, 95wt.%, 98wt.%, etc. The carbon content of the three-dimensional porous material 1 can be determined by a carbon-sulfur analyzer.
[0056] Accordingly, in some embodiments of the present application, the preparation of the three-dimensional porous material 1 may include: providing a base material, making pores in the base material, and obtaining the three-dimensional porous material 1 provided in the embodiments of the present application. The base material includes but is not limited to a carbon precursor, a ceramic precursor, and a metal precursor.
[0057] In some embodiments of the present application, the above-mentioned base material is a carbon precursor. In this case, the preparation of the three-dimensional porous material 1 may include:
[0058] S01, placing a carbon precursor in a reaction chamber, keeping it warm at a first temperature for a first time, cooling it to room temperature, and then washing, drying and crushing it in sequence to obtain a three-dimensional porous material 1. The above preparation method has simple steps, strong process reliability, and can achieve large-scale industrial production. In some specific embodiments of the present application, the material obtained after keeping warm for the first time is naturally cooled to room temperature.
[0059] In some embodiments of the present application, the carbon precursor includes but is not limited to at least one of coke, biomass carbon raw materials or chemical organic polymer materials. Among them, the coke includes but is not limited to coal coke, petroleum coke, etc. The biomass carbon raw materials include but are not limited to at least one of coconut shell, bamboo, apricot shell, starch or lignin. The organic polymer material includes but is not limited to at least one of phenolic resin, epoxy resin, polyethylene, polycarbonate, polyphenylene ether or rubber.
[0060] In some embodiments of the present application, when the carbon precursor is coke, the process further includes mixing the coke with an alkaline activator and then subjecting the mixture to a heat preservation treatment at a first temperature. The alkaline activator includes but is not limited to at least one of sodium hydroxide, potassium hydroxide or potassium carbonate.
[0061] In some specific embodiments of the present application, the carbon precursor is coke, at this time, the first temperature is 500°C-1200°C, and the first time is 1h-48h. Specifically, the first temperature may be, but is not limited to, 500°C, 550°C, 600°C, 650°C, 700°C, 750°C, 800°C, 850°C, 900°C, 950°C, 1000°C, 1050°C, 1100°C, 1150°C, 1200°C, etc. Specifically, the first time may be, but is not limited to, 1h, 2h, 5h, 8h, 10h, 12h, 15h, 18h, 20h, 22h, 25h, 28h, 30h, 32h, 35h, 38h, 40h, 42h, 45h, 48h, etc. Specifically, coke and alkaline activator are mixed in a mass ratio of 1: (1-20) and kept at 500°C-1200°C for 1h-48h. In some specific embodiments, coke and alkaline activator are mixed in a mass ratio of 1: (2-5) and kept at 500°C-1200°C for 1h-48h. In this way, it is more conducive to regulating the opening diameter and distribution of the three-dimensional porous material 1. Specifically, the mass ratio of coke and activator can be 1:1, 1:2, 1:3, 1:4, 1:5, 1:8, 1:10, 1:12, 1:15, 1:18, 1:20, etc.
[0062] In some specific embodiments of the present application, the carbon precursor is at least one of a biomass carbon raw material or an organic polymer material. At this time, in step S01, the first temperature is 500°C-1200°C, and the first time is 0.5h-5h; and before the heat preservation treatment at the first temperature, the biomass carbon raw material and / or the organic polymer material are carbonized, and when the heat preservation treatment is performed at the first temperature, an activation aid is introduced into the reaction chamber, and the activation aid includes but is not limited to at least one of water vapor, carbon dioxide or water gas. Specifically, when the carbon precursor is a biomass carbon raw material and / or an organic polymer material, the first temperature is but not limited to 500°C, 550°C, 600°C, 650°C, 700°C, 750°C, 800°C, 850°C, 900°C, 950°C, 1000°C, 1050°C, 1100°C, 1150°C, 1200°C, etc.; the first insulation time can be but not limited to 0.5h, 1.0h, 1.5h, 2.0h, 2.5h, 3.0h, 3.5h, 4.0h, 4.5h, 5.0h, etc.
[0063] In some specific embodiments, the above step S01 includes: placing the biomass carbon raw material and / or the organic polymer material in a reaction chamber and keeping it at 300℃-1000℃ for 0.5h-10h to carbonize it, then introducing an activating agent into the reaction chamber, and keeping it at 500℃-1200℃ for 0.5h-5h to make holes on the carbonized biomass carbon raw material and / or the carbonized organic polymer material, and after cooling, drying and crushing, a three-dimensional porous material 1 is obtained. Wherein, when the activating agent is introduced into the reaction chamber, the gas flow rate of the activating agent is in the range of 1mL / min-20mL / min. Specifically, the gas flow rate of the activating agent can be, but is not limited to, 1mL / min, 2mL / min, 3mL / min, 5mL / min, 8mL / min, 10mL / min, 12mL / min, 15mL / min, 18mL / min, 20mL / min, etc.
[0064] In some specific embodiments of the present application, when the carbon precursor is an organic polymer material such as a thermoplastic phenolic resin, a cross-linking curing treatment is also included before the carbonization treatment. For example, the thermoplastic phenolic resin is mixed with phenol formaldehyde and heat-insulated at 50°C-200°C to cure the thermoplastic phenolic resin, thereby making it more conducive to the subsequent carbonization treatment. A person of ordinary skill in the art can select the type of carbon precursor of the three-dimensional porous material 1 according to actual needs, and select a suitable preparation process for the selected carbon precursor.
[0065] In some embodiments of the present application, step S02 is also included: in a protective atmosphere, the product obtained after crushing in step S01 is subjected to a heat preservation treatment at a second temperature to obtain a three-dimensional porous material 1; wherein the second temperature is in the range of 400°C-2000°C. In this way, impurity functional groups (for example, hydroxyl groups, carboxyl groups, oxygen atoms, nitrogen atoms, etc.) in the three-dimensional porous material 1 can be removed, thereby increasing the carbon content of the three-dimensional porous material 1 and avoiding the impurity functional groups from affecting the adsorption and deposition of particles during the application of the three-dimensional porous material 1. Specifically, the second temperature can be, but is not limited to, 400°C, 500°C, 800°C, 1000°C, 1200°C, 1500°C, 1800°C, 2000°C, etc.
[0066] See also Figure 2 The embodiment of the present application also provides a negative electrode composite material 100, comprising the three-dimensional porous material 1 provided in the embodiment of the present application and a plurality of nanoparticles 30 located in the openings of the three-dimensional porous material 1; wherein the material of the nanoparticles 30 comprises at least one of a silicon-containing material, a phosphorus-containing material or a tin-containing material. In the embodiment of the present application, the material of the nanoparticles 30 may be a crystalline phase or an amorphous phase, which may be selected according to the actual application.
[0067] In the embodiment of the present application, the negative electrode composite material 100 is pretreated so that the nanoparticles 30 are separated from the three-dimensional porous material 1, and the three-dimensional porous material 1 is obtained, and then the gas adsorption and desorption test is used to measure the opening diameter distribution of the three-dimensional porous material 1. In the embodiment of the present application, an energy dispersive spectrometer (EDS) test can be used to characterize the distribution of the nanoparticles 30 in the negative electrode composite material 100.
[0068] The materials of the above-mentioned nanoparticles 30 are all high-performance electrode active materials, which can provide a higher reversible capacity for the battery based on their inherent properties. In addition, based on the special opening diameter and distribution design of the three-dimensional porous material 1, the average particle size of the nanoparticles 30 is relatively small, which can effectively reduce the expansion rate of the negative electrode composite material 100 during the charge and discharge cycle; at the same time, the concentration of multiple nanoparticles 30 in the negative electrode composite material 100 within a smaller particle size range is relatively high (the uniformity of the negative electrode composite material 100 is better), so the uniformity of the internal mechanical stress distribution of the negative electrode composite material 100 during the battery cycle can be improved, and the risk of rupture of the negative electrode composite material 100 can be reduced, thereby improving the cycle performance of the battery.
[0069] In the embodiments of the present application, the silicon-containing material includes but is not limited to silicon, silicon dioxide (SiOx), and silicon-carbon composites; the phosphorus-containing material includes but is not limited to phosphorus; and the tin-containing material includes but is not limited to tin and tin alloys.
[0070] In some embodiments of the present application, the nanoparticles 30 are located in the openings of the three-dimensional porous material 1 with an opening diameter of ≥1nm. Thanks to the deposition and adsorption characteristics of the three-dimensional porous material 1 provided in the embodiment of the present application, the nanoparticles 30 are more easily deposited in the openings with an opening diameter of ≥1nm. In addition, this characteristic can also make the negative electrode composite material 100 have "empty holes" (openings without nanoparticles 30), so that a buffer space can be provided for the expansion of the nanoparticles 30 in the negative electrode composite material 100, thereby reducing the volume change of the negative electrode composite material 100 during the battery cycle, which is more conducive to the final battery cycle performance. In some cases, nanoparticles 30 may also exist in the openings (second type pores 12) with an opening diameter <1nm. At this time, the particle size of the nanoparticles 30 in the second type pores 12 is very small and the content is very small.
[0071] In some embodiments of the present application, the size of the nanoparticles 30 in at least one direction is ≤2nm. This is more conducive to suppressing the volume change of the negative electrode composite material 100 during the battery cycle. Further, in some embodiments, the particle size of the nanoparticles 30 is ≤2nm.
[0072] In some embodiments of the present application, in the negative electrode composite material 100, based on the total open pore volume of the three-dimensional porous material 1, the volume proportion of the plurality of micropores 10 is ≥ 85%. In this way, the average particle size of the nanoparticles 30 in the negative electrode composite material 100 can be further reduced, and the particle size uniformity in the negative electrode composite material 100 can be improved, thereby further reducing the expansion rate of the negative electrode composite material 100 during the battery cycle and improving the uniformity of the negative electrode composite material 100.
[0073] In some embodiments of the present application, in the negative electrode composite material 100, the volume proportion of the plurality of third-type pores 20 is less than 1% based on the total open pore volume of the three-dimensional porous material 1. Limiting the proportion of the third-type pores 20 is conducive to reducing the average particle size of the nanoparticles 30, thereby optimizing the electrochemical performance of the negative electrode composite material 100.
[0074] In some embodiments of the present application, in the negative electrode composite material 100, based on the total open pore volume of the three-dimensional porous material 1, the volume proportion of the plurality of second-type pores 12 is ≤40%. In this way, the mass proportion of the nanoparticles 30 in the negative electrode composite material 100 can be increased, thereby increasing the reversible capacity of the negative electrode composite material 100, and thus increasing the energy density of the battery.
[0075] In some embodiments of the present application, the mass of the plurality of nanoparticles 30 accounts for 30%-80% of the total mass of the negative electrode composite material 100. In some specific embodiments, the mass of the plurality of nanoparticles 30 accounts for 40%-50% of the total mass of the negative electrode composite material 100. In combination with the special structural design of the negative electrode composite material 100 provided in the embodiment of the present application, the mass proportion of the nanoparticles 30 (that is, the high-performance electrode material) is controlled within the above range, so that the negative electrode composite material 100 can take into account both a higher reversible capacity and a lower expansion rate, and can be used to provide a battery with both high energy density and better cycle performance. Specifically, the mass of the nanoparticles 30 may account for 30%, 32%, 35%, 40%, 41%, 42%, 43%, 44%, 45%, 46%, 47%, 48%, 49%, 50%, 51%, 52%, 53%, 54%, 55%, 56%, 57%, 58%, 59%, 60%, 65%, 68%, 70%, 72%, 75%, 78%, 80%, etc. of the total mass of the negative electrode composite material 100. In the embodiment of the present application, a thermogravimetric analysis test (TGA), an X-ray fluorescence spectrometer (XRF) or an energy dispersive spectrometer (EDS) may be used to test the mass proportion of the plurality of nanoparticles 30 in the negative electrode composite material 100.
[0076] In some embodiments of the present application, when the material of the three-dimensional porous material is amorphous carbon and the nanoparticles 30 are doped or undoped silicon, the true density of the negative electrode composite material 100 is in the range of 1.85 g / cc-2.30 g / cc. In the embodiments of the present application, the true density of the three-dimensional porous material is tested by the gas volume method. In addition, in some cases, there are closed pores in the negative electrode composite material 100. At this time, limiting its true density also limits the volume proportion of the closed pores in the negative electrode composite material 100 to a suitable range to a certain extent. The true density of the negative electrode composite material 100 may be, but is not limited to, 1.50 g / cc, 1.55 g / cc, 1.60 g / cc, 1.65 g / cc, 1.70 g / cc, 1.75 g / cc, 1.80 g / cc, 1.85 g / cc, 1.88 g / cc, 1.89 g / cc, 1.90 g / cc, 1.91 g / cc, 1.92 g / cc, 1.93 g / cc, 1.94 g / cc, 1.95 g / cc, 2.00 g / cc, 2.05 g / cc, 2.05 g / cc, 2.10 g / cc, 2.15 g / cc, 2.20 g / cc, 2.25 g / cc, 2.30 g / cc, etc.
[0077] In some implementations of this application, please see Figure 3A as well as Figure 3B , the negative electrode composite material 100 also includes a coating layer 40 formed on the surface of the three-dimensional porous material 1, the coating layer 40 includes a carbon coating layer and / or a fast ion conductor coating layer, or the coating layer 40 is a composite coating layer, and the material of the composite coating layer includes a carbon material and a fast ion conductor material. The carbon coating layer can improve the electronic conductivity of the negative electrode composite material 100 and contribute to the capacity, and the fast ion conductor coating layer can improve the ion conductivity of the negative electrode composite material 100, thereby improving the rate performance of the battery and improving the fast charging performance of the battery; the composite coating layer can simultaneously improve the electronic conductivity and ion conductivity of the composite material. In addition, the coating layer 40 can be used as a physical isolation to effectively reduce the risk of silicon-containing materials, phosphorus-containing materials, and tin-containing materials being exposed to the surface of the negative electrode composite material 100, thereby reducing the side reactions during the battery cycle (for example, in a liquid battery, the side reactions between silicon-containing materials and electrolytes), thereby improving the interface stability of the negative electrode composite material 100, which is more conducive to the performance of the battery. Furthermore, the three-dimensional porous material containing nanoparticles 30 is equivalent to the "core" of the negative electrode composite material 100. At this time, the coating layer on the surface of the three-dimensional porous material can also inhibit the expansion of the "core", thereby further reducing the expansion rate of the negative electrode composite material 100 during the charge and discharge cycle.
[0078] In some embodiments of the present application, a carbon coating layer and a fast ion conductor coating layer are sequentially formed on the surface of the three-dimensional porous material 1, or a fast ion conductor coating layer and a carbon coating layer are sequentially formed on the surface of the three-dimensional porous material 1. Those skilled in the art can make a selection according to practical applications.
[0079] In the embodiment of the present application, the material of the fast ion conductor coating layer (fast ion conductor material) can be any fast ion conductor material known in the art. Taking the fast ion conductor material for lithium ion battery as an example, it includes but is not limited to Li3N, Li 14 Zn, etc. Taking fast ion conductors for sodium ion batteries as an example, they include but are not limited to Na3Zr2Si2PO 12 , Na2O·Al2O3, etc.
[0080] In some specific embodiments of the present application, the material (carbon material) of the carbon coating layer includes amorphous carbon. The amorphous carbon coating layer can be characterized by a transmission electron microscope (TEM), see Figure 7 , Figure 7 This is a TEM photograph of the negative electrode composite material 100 provided in one embodiment of the present application, in which a clear amorphous carbon coating layer can be seen.
[0081] In some embodiments of the present application, the thickness of the coating layer 40 is ≤20nm. Controlling the thickness within the above range can achieve a physical isolation effect, and can also shorten the diffusion path of ions or electrons in the negative electrode composite material 100, which can ensure that the final battery has a better rate performance. Specifically, the thickness of the coating layer 40 can be, but is not limited to, 1nm, 2nm, 5nm, 8nm, 10nm, 12nm, 15nm, 18nm, 20nm, etc.
[0082] In the embodiment of the present application, the fast ion conductor coating layer can be formed on the surface of the three-dimensional porous material 1 (ie, the negative electrode composite material 100 ) by any process known in the art, such as ball milling.
[0083] In the embodiment of the present application, the carbon coating layer can be formed on the surface of the three-dimensional porous material 1 (ie, the negative electrode composite material 100 ) by any process known in the art, such as vapor deposition and ball milling.
[0084] In some implementations of this application, please see Figure 3B, the carbon coating layer 40 is also formed in the openings of the three-dimensional porous material 1. The carbon coating layer formed in the openings of the three-dimensional porous material 1 may include the following situations: (1) the carbon coating layer is formed in the openings where the nanoparticles 30 are deposited. In some specific embodiments, the carbon coating layer is also fully or partially coated on the surface of the nanoparticles 30. (2) the carbon coating layer is formed in the openings that do not contain the nanoparticles 30 and is attached to the inner wall of the openings of the three-dimensional porous material 1; in some specific embodiments, the carbon coating layer also partially fills or fully fills the openings. At this time, the voids in a portion of the negative electrode composite material 100 can be reduced, and the contact between the nanoparticles 30 and the three-dimensional porous material can be increased, thereby facilitating the transmission of electrons and ions in the negative electrode composite material 100, further inhibiting the expansion of the nanoparticles 30, and contributing to part of the reversible capacity.
[0085] In some embodiments of the present application, a carbon coating layer can be formed in the open pores of the three-dimensional porous material 1 by vapor deposition. It can be understood that the vapor deposition process can also form a carbon coating layer on the surface of the three-dimensional porous material at the same time. That is, in some embodiments, a carbon coating layer is formed on the surface of the three-dimensional porous material 1 and in the open pores of the three-dimensional porous material 1.
[0086] In some embodiments of the present application, the negative electrode composite material 100 contains a doping element, wherein the doping element is at least one of N, P or S. Doping can improve the electrochemical performance of the negative electrode composite material 100 .
[0087] In some embodiments of the present application, the nanoparticles 30 contain the above-mentioned doping elements. Doping is beneficial to the charge transfer and ion diffusion of the nanoparticles 30, and can also improve the stability of the material of the nanoparticles 30, thereby improving the electrochemical performance of the negative electrode composite material 100. Specifically, when the nanoparticles 30 are silicon-containing materials, the nanoparticles 30 include but are not limited to silicon single substance doped with N, silicon single substance doped with P, silicon single substance doped with S, etc.; when the nanoparticles 30 are phosphorus-containing materials, the nanoparticles 30 include but are not limited to phosphorus single substance doped with S atoms; when the nanoparticles 30 are tin-containing materials, the nanoparticles 30 include but are not limited to Si-N alloys. The above is just an enumeration and does not constitute a limitation on the elemental composition of the negative electrode composite material 100 provided in the embodiments of the present application.
[0088] In some embodiments of the present application, the three-dimensional porous material 1 contains the above-mentioned doping elements. In this way, at least the conductivity of the negative electrode composite material 100 can be improved. Specifically, when the material of the three-dimensional porous material 1 is conductive carbon, the doping element can be at least one of N, S or P. Specifically, for example: the negative electrode composite material 100 can be an N-doped phosphorus / carbon composite material, and the phosphorus nanoparticles are located in the N-doped three-dimensional porous carbon; the negative electrode composite material 100 can be a P-doped tin / carbon composite material, and the tin nanoparticles are located in the P-doped three-dimensional porous carbon. The above is only an example and does not limit the composition of the negative electrode composite material 100 provided in the embodiment of the present application. Those skilled in the art can make a choice according to the actual application.
[0089] In some embodiments of the present application, the three-dimensional porous material 1 and the nanoparticles 30 simultaneously contain the above-mentioned doping elements. For example, the negative electrode composite material 100 is an N-doped silicon / carbon composite material, wherein the N-doped silicon single substance nanoparticles are located in the N-doped three-dimensional porous carbon; for another example, the negative electrode composite material 100 is an S-doped phosphorus / carbon composite material, wherein the S-doped silicon single substance nanoparticles are located in the S-doped three-dimensional porous carbon. The above is only an example and does not limit the composition of the negative electrode composite material 100 provided in the embodiment of the present application. Those skilled in the art can make a selection according to practical applications.
[0090] In some embodiments of the present application, the three-dimensional porous material 1, the nanoparticles 30 and the carbon coating layer contain the above doping elements at the same time. A person skilled in the art can select them according to application requirements.
[0091] In some embodiments of the present application, the mass proportion of the above-mentioned doping elements in the negative electrode composite material 100 is less than 10%. In this way, the electronic conductivity and reversible capacity of the negative electrode composite material can be taken into account. Specifically, the mass proportion of the above-mentioned doping elements in the negative electrode composite material 100 can be 0.1%, 0.5%, 1.0%, 2.0%, 3.0%, 4.0%, 5.0%, 6.0%, 7.0%, 8.0%, 9.0%, 9.5%, 9.8%, etc. In the embodiment of the present application, XRF or EDS can be used to test the mass proportion of the doping elements in the negative electrode composite material.
[0092] In some embodiments of the present application, the D50 of the negative electrode composite material 100 is in the range of 2μm-15μm. In some specific embodiments, the D50 of the negative electrode composite material 100 is in the range of 7μm-8μm. Specifically, the D50 of the negative electrode composite material 100 may be, but is not limited to, 2μm, 3μm, 4μm, 5μm, 6μm, 7μm, 8μm, 9μm, 10μm, 11μm, 12μm, 13μm, 14μm, 15μm, etc. When the D50 of the negative electrode composite material 100 is within the above range, the length of the deintercalation path of the active ions can be controlled within a reasonable range, which is beneficial to the performance of the battery. In the embodiments of the present application, the above-mentioned D50 refers to the particle size corresponding to the cumulative particle size distribution percentage of the negative electrode composite material 100 reaches 50%, and the D50 of the negative electrode composite material 100 is tested using a laser particle size analyzer.
[0093] In some embodiments of the present application, the preparation of the negative electrode composite material 100 includes: S01, depositing nanoparticles in the three-dimensional porous material 1 provided in the embodiment of the present application. The preparation method has a simple process and strong controllability, high production efficiency, and can achieve large-scale industrial production. In addition, the mass proportion of nanoparticles in the negative electrode composite material can be adjusted by adjusting the parameters in the deposition process. For example, the mass proportion of nanoparticles can be adjusted by adjusting the insulation time; for example, when the deposited raw material is in a gaseous state, the mass proportion of nanoparticles can also be adjusted by adjusting the flow rate of the deposited raw material.
[0094] In some embodiments of the present application, the above deposition can be vapor deposition, or sputtering deposition, etc., and those skilled in the art can select according to practical applications. The raw materials of the nanoparticles can be selected according to practical applications.
[0095] It should be noted that, since the above-mentioned negative electrode composite material is prepared by depositing nanoparticles 30 in the three-dimensional porous material 1, in some embodiments of the present application, nanoparticle material is also deposited on the surface of the three-dimensional porous material 1 (not shown in the figure). Specifically, the above-mentioned nanoparticle material can be distributed in the form of particles on the surface of the three-dimensional porous material 1, and / or partially coated on the surface of the three-dimensional porous material 1 in the form of a continuous phase.
[0096] The following is a brief description of step S01 using the example that the material of the nanoparticles 30 is silicon and the material of the three-dimensional porous material 1 is amorphous carbon: the three-dimensional porous material 1 is placed in a reaction chamber, a protective gas (e.g., nitrogen) is introduced to exhaust the air, and the three-dimensional porous material 1 is preheated to 400°C-500°C under a protective atmosphere, and then monosilane gas is introduced into the reaction chamber, and the temperature is kept for 2h-3h to achieve the deposition of silicon nanoparticles, and then the temperature is naturally lowered to room temperature, and the material is discharged to obtain the negative electrode composite material 100. In some cases, after the temperature in the reaction chamber drops to room temperature, a mixed gas of oxygen and nitrogen (the oxygen content in the mixed gas is <10%) is introduced into the reaction chamber to pre-oxidize and passivate the negative electrode composite material 100 to prevent it from suddenly contacting with air and causing oxidation and exothermic combustion of silicon nanoparticles, thereby improving the stability of the negative electrode composite material. It should be noted that, in some specific embodiments, granular silicon is deposited on the surface of the negative electrode composite material 100 (ie, the surface of the three-dimensional porous material 1 ), and / or a silicon layer is formed on part of the surface of the negative electrode composite material 100 .
[0097] In some embodiments of the present application, the preparation of the negative electrode composite material 100 further includes step S02: forming a coating layer on the surface of the three-dimensional porous material on which the nanoparticles are deposited. Specifically, any process known in the art can be used to form the coating layer on the surface of the three-dimensional porous material on which the nanoparticles are deposited. Specifically, it includes but is not limited to ball milling.
[0098] In some cases, the three-dimensional porous material 1 deposited with nanoparticles 30 can be placed in a ball mill together with a carbon material to obtain a negative electrode composite material 100 having a carbon coating layer on the surface. In other cases, the three-dimensional porous material 1 deposited with nanoparticles 30 can be placed in a ball mill together with a fast ion conductor material to obtain a negative electrode composite material 100 having a fast ion conductor coating layer on the surface. In still other cases, the three-dimensional porous material 1 deposited with nanoparticles, a carbon material, and a fast ion conductor material can be placed in a ball mill together to obtain a negative electrode composite material 100 having a composite coating layer on the surface.
[0099] In some other embodiments of the present application, step S02 is: forming a carbon coating layer simultaneously on the surface and in the openings of the three-dimensional porous material 1 on which the nanoparticles 30 are deposited. In some specific embodiments, the three-dimensional porous material 1 on which the nanoparticles 30 are deposited is placed in a reaction chamber (a reaction chamber without air), a carbon source is introduced at 600°C-800°C, and the temperature is kept for 0.5h-4h, so that the carbon material is deposited in the openings of the three-dimensional porous material 1 to form a carbon coating layer, and then naturally cooled to room temperature to obtain the negative electrode composite material 100. The above-mentioned carbon source includes but is not limited to methane, ethane, acetylene, benzene, amines, etc.
[0100] In some embodiments of the present application, step S03 is further included: doping the material obtained in step S01 with elements, or doping the material obtained in step S02 with elements. That is, doping is performed on the three-dimensional porous material 1 deposited with nanoparticles 30, or doping is performed on the three-dimensional porous material 1 deposited with nanoparticles 30 and having a coating layer 40. The doping process can be any well-known process in the art, and a person of ordinary skill in the art can select one according to actual application.
[0101] In some specific embodiments of the present application, the preparation of the negative electrode composite material includes the following steps:
[0102] S01, placing the three-dimensional porous material 1 in a reaction chamber, introducing nitrogen to exhaust the air in the reaction chamber, and preheating the three-dimensional porous material to 400° C.-500° C. in a nitrogen atmosphere; then introducing monosilane gas into the reaction chamber, and keeping the temperature at 400° C.-500° C. for 2 h-3 h;
[0103] S02, cut off the monosilane gas, raise the temperature to 600°C-800°C, introduce a gaseous carbon source into the reaction chamber, and keep the temperature at 600°C-800°C for 0.5h-4h;
[0104] S03. Replace the gaseous carbon source with nitrogen, keep warm at 600°C-800°C for 0.5h-2h, cool naturally to room temperature, and discharge the material to obtain a N-doped silicon / carbon negative electrode composite material.
[0105] The embodiment of the present application also provides a negative electrode plate, including a current collector and a negative electrode material layer disposed on the surface of the current collector, wherein the negative electrode material layer includes the negative electrode composite material 100 provided in the embodiment of the present application. Due to the use of the negative electrode composite material 100 provided in the embodiment of the present application, the negative electrode plate has a low volume expansion rate after battery cycling and can provide a higher reversible capacity, thereby being used to provide a secondary battery with both higher energy density and better cycle performance.
[0106] In the embodiments of the present application, the above-mentioned current collector is selected from any known negative electrode current collector for secondary batteries in the field, and the present application does not impose any limitation on this.
[0107] In some embodiments of the present application, the negative electrode active material layer includes the negative electrode composite material, a binder, and an optional conductive agent. The binder can be selected from any known binder in the art. The conductive agent can also be selected from any known conductive agent in the art.
[0108] In some embodiments of the present application, the negative electrode active material layer may also include other negative electrode materials commonly used in the field. That is, a mixture of the negative electrode composite material provided in the embodiment of the present application and other negative electrode materials commonly used in the field is used as the negative electrode active material.
[0109] The embodiment of the present application also provides a secondary battery, including a negative electrode sheet, a positive electrode sheet, and an electrolyte located between the positive electrode sheet and the negative electrode sheet. Due to the use of the negative electrode sheet provided in the embodiment of the present application, the secondary battery can have both high energy density and good cycle performance.
[0110] In the embodiment of the present application, the secondary battery may be a lithium ion battery, a sodium ion battery, etc., but is not limited thereto.
[0111] In some embodiments of the present application, the secondary battery is a liquid battery, which includes a negative electrode plate, a positive electrode plate, and a separator and an electrolyte located between the positive electrode plate and the negative electrode plate.
[0112] In some embodiments of the present application, the secondary battery is a liquid battery, which includes a negative electrode plate, a positive electrode plate, and a solid electrolyte located between the positive electrode plate and the negative electrode plate.
[0113] In some other embodiments of the present application, the secondary battery is a semi-solid battery.
[0114] The embodiment of the present application also provides an electric device, including the secondary battery provided in the embodiment of the present application. The electric device includes but is not limited to 3C electronic products, such as mobile phones, laptops, tablet computers, drones, wearable electronic devices, etc. The electric device may also include power vehicles, such as new energy vehicles, electric bicycles, etc.
[0115] The embodiment of the present application also provides an energy storage system, including the secondary battery provided in the embodiment of the present application. Due to the use of the secondary battery provided in the embodiment of the present application, the energy storage system can have a higher energy density.
[0116] In some embodiments of the present application, the energy storage system includes an electrically connected energy storage device and a power converter, the energy storage device includes a housing cavity and the secondary battery accommodated in the housing cavity, the power converter is used to perform power conversion processing on the voltage and / or current, and input the changed voltage and / or current to the energy storage device, so that the energy storage device can meet the power requirements of the electrical equipment.
[0117] The technical solution of the embodiment of the present application is described in detail below in multiple embodiments.
[0118] Example 1
[0119] The three-dimensional porous material prepared in the embodiment of the present application has a carbon content of >90wt.% and a total pore volume of 0.87cm 3 / g, taking the total open pore volume of the three-dimensional porous material as the benchmark, the volume of micropores (openings with an opening diameter ≤ 2nm) accounts for 91%, the volume of the first type of pores (openings with an opening diameter of 1nm-2nm) accounts for 57%, the volume of the second type of pores (openings with an opening diameter <1nm) accounts for 34%, and the volume of the third type of pores (openings with an opening diameter >5nm) accounts for 0.5%.
[0120] Example 2
[0121] The difference from the three-dimensional porous material in Example 1 is that the total pore volume is 0.86 cm 3 / g, taking the total open pore volume of the three-dimensional porous material as the benchmark, the volume share of micropores (openings with an opening diameter ≤ 2nm) is 89%, the volume share of the first type of pores (openings with an opening diameter of 1nm-2nm) is 51%, the volume share of the second type of pores (openings with an opening diameter <1nm) is 38%, and the volume share of the third type of pores (openings with an opening diameter >5nm) is 0.6%.
[0122] Example 3
[0123] The difference from the three-dimensional porous material in Example 1 is that the total pore volume is 0.84 cm 3 / g, taking the total open pore volume of the three-dimensional porous material as the benchmark, the volume of micropores (openings with an opening diameter ≤ 2nm) accounts for 87%, the volume of the first type of pores (opening diameter of 1nm-2nm) accounts for 50%, the volume of the second type of pores (opening diameter <1nm) accounts for 37%, and the volume of the third type of pores (opening diameter>5nm) accounts for 0.7%.
[0124] In order to highlight the beneficial effects of the embodiments of the present application, the following comparative examples are now provided.
[0125] Comparative Example 1
[0126] Provided is a three-dimensional porous material with a carbon content of >90wt.% and a total pore volume of 0.85cm 3 / g, taking the total open pore volume of the three-dimensional porous material as the benchmark, the volume of micropores (openings with an opening diameter ≤ 2nm) accounts for 86%, the volume of the first type of pores (opening diameter of 1nm-2nm) accounts for 33%, the volume of the second type of pores (opening diameter <1nm) accounts for 53%, and the volume of the third type of pores (opening diameter >5nm) accounts for 1.8%.
[0127] Comparative Example 2
[0128] Provided is a three-dimensional porous material with a carbon content of >90wt.% and a total pore volume of 0.86cm 3 / g, taking the total open pore volume of the three-dimensional porous material as the benchmark, the volume of micropores (openings with an opening diameter ≤ 2nm) accounts for 74%, the volume of the first type of pores (openings with an opening diameter of 1nm-2nm) accounts for 38%, the volume of the second type of pores (openings with an opening diameter <1nm) accounts for 36%, and the volume of the third type of pores (openings with an opening diameter >5nm) accounts for 9.8%.
[0129] It should be noted that the opening diameter distribution of the three-dimensional porous materials of the above-mentioned embodiments and comparative examples is determined by nitrogen elution gas adsorption and desorption test: the three-dimensional porous materials of the above-mentioned embodiments and comparative examples are placed in a gas adsorption and desorption tester, degassed at 200°C for 16 hours to obtain the opening diameter distribution and calculate the specific surface area, and the specific surface area results are summarized in Table 1. For ease of reading, the opening diameter distribution of the three-dimensional porous materials of the embodiments and comparative examples is also summarized in Table 1.
[0130] The carbon content of the three-dimensional porous materials of the above-mentioned embodiments and comparative examples was measured by a carbon-sulfur analyzer.
[0131] Deposition of silicon nanoparticles in three-dimensional porous materials
[0132] The three-dimensional porous materials provided in the above embodiments and comparative examples were placed in a rotary tube furnace, nitrogen was passed through for 1 hour to exhaust the air in the rotary tube furnace, and the three-dimensional porous materials were preheated to 420° C. in a nitrogen atmosphere; monosilane gas was then passed through the rotary tube furnace, and the temperature was kept at 420° C. for 2 hours;
[0133] After cooling to room temperature, a mixed gas of oxygen and nitrogen was introduced into the rotary tube furnace, wherein the oxygen content in the mixed gas was less than 10%, and the material was discharged after 30 minutes. The negative electrode composite materials prepared from the three-dimensional porous materials of each embodiment were respectively recorded as S1-S3, and the negative electrode composite materials prepared from the three-dimensional porous materials of each comparative example were respectively recorded as DS1 and DS2.
[0134] Preparation of negative electrode composite materials with carbon coating
[0135] The three-dimensional porous materials provided in the above embodiments and comparative examples were placed in a rotary tube furnace, nitrogen was passed through for 1 hour to exhaust the air in the rotary tube furnace, and the three-dimensional porous materials were preheated to 420° C. in a nitrogen atmosphere; monosilane gas was then passed through the rotary tube furnace, and the temperature was kept at 420° C. for 2 hours;
[0136] The monosilane gas was cut off, and the temperature was raised to 650°C. A gaseous carbon source was introduced into the rotary tube furnace, and the temperature was kept at 650°C for 3 hours. The negative electrode composite materials prepared from the three-dimensional porous materials of each embodiment were respectively recorded as SC1-SC3, and the negative electrode composite materials prepared from the three-dimensional porous materials of each comparative example were respectively recorded as DSC1 and DSC2.
[0137] Preparation of N-doped anode composite materials with carbon coating
[0138] The three-dimensional porous material of Example 1 is placed in a rotary tube furnace, nitrogen is passed through for 1 hour to exhaust the air in the rotary tube furnace, and the three-dimensional porous material is preheated to 420° C. in a nitrogen atmosphere; monosilane gas is then passed through the rotary tube furnace, and the temperature is kept at 420° C. for 2 hours;
[0139] Cut off the monosilane gas, raise the temperature to 650°C, introduce a gaseous carbon source (specifically methane) into the rotary tube furnace, keep the temperature at 650°C for 3 hours, cool naturally to room temperature, and discharge the material;
[0140] The temperature was kept constant, and methane was replaced with nitrogen. The temperature was kept constant for 0.5 h, and then naturally cooled to room temperature. The negative electrode composite material prepared from the three-dimensional porous material in Example 1 was recorded as SCN1.
[0141] Changing the deposition time of monosilane to prepare negative electrode composite materials with different silicon contents from SC1
[0142] Case SC1-2
[0143] The three-dimensional porous material provided in Example 1 is placed in a rotary tube furnace, nitrogen is passed through for 1 hour to exhaust the air in the rotary tube furnace, and the three-dimensional porous material is preheated to 420° C. in a nitrogen atmosphere; monosilane gas is then passed through the rotary tube furnace, and the temperature is kept at 420° C. for 1.9 hours;
[0144] The monosilane gas was cut off, and the temperature was raised to 650°C. A gaseous carbon source was introduced into the rotary tube furnace, and the temperature was kept at 650°C for 3 hours. The furnace was naturally cooled to room temperature and discharged to obtain the negative electrode composite material SC1-2.
[0145] Case SC1-3
[0146] The only difference from case SC1-2 is that monosilane gas is introduced into the rotary tube furnace and kept at 420° C. for 1.8 h. Thus, negative electrode composite material SC1-3 is obtained.
[0147] Structural parameters and electrochemical performance characterization
[0148] 1) Structural parameter characterization
[0149] ① The X-ray fluorescence scattering analyzer was used to test the mass proportion of silicon element in each negative electrode composite material in S1-S3, DS1, DS2 and SC1-SC3, DSC1, DSC2, SCN1 and SC1-1 to SC1-3. The results are summarized in Tables 2 to 5 respectively.
[0150] ② The D50 of S1-S3, DS1, DS2, SC1-SC3, DSC1, DSC2 and SCN1 were tested by laser particle size analyzer, and the results are summarized in Tables 2 to 5 respectively.
[0151] ③ The true densities of S1-S3, DS1, DS2, SC1-SC3, DSC1, DSC2, SCN1 and SC1-1 to SC1-3 were tested using a fully automatic gas replacement true density tester. The results are summarized in Tables 2 to 5 respectively.
[0152] ④ The powder resistivity of S1-S3, DS1, DS2, SC1-SC3, DSC1, DSC2, SCN1 and SC1-1 to SC1-3 was tested using a powder resistivity tester, and the results are summarized in Tables 2 to 5 respectively.
[0153] ⑤ The nitrogen adsorption-desorption test was used to determine the specific surface areas of S1-S3, DS1, DS2 and SC1-SC3, DSC1, DSC2, SCN1 and SC1-1 to SC1-3. The results are summarized in Tables 2 to 5 respectively.
[0154] ⑥ Thermogravimetric analysis (TGA) was used to determine the silicon content in S1-S3, DS1, DS2, SC1-SC3, DSC1, DSC2, SCN1, and SC1-1 to SC1-3, and the results are summarized in Tables 2 to 5, respectively.
[0155] ⑦ TEM was used to observe SC1-SC3, DSC1, and DSC2. The TEM photo of SC1 is shown in the figure. Figure 7 As shown, a clear amorphous carbon coating is visible.
[0156] ⑧ X-ray diffraction (XRD) was used to test the negative electrode composite material SC1 and the comparative negative electrode composite material DSC2. The XRD spectra of SC1 and DSC2 are as follows: Figure 4 As shown, clear characteristic peaks of amorphous carbon can be seen.
[0157] ⑨ The morphology of the negative electrode composite material SC1 and the comparative negative electrode composite material DSC2 and the distribution of silicon elements at the corresponding positions were observed using a scanning electron microscope (SEM)-energy dispersive spectrometer (EDS); the SEM photos of SC1 and DSC2 and the corresponding EDS silicon element distribution maps are summarized in Figure 5 and Figure 6 middle.
[0158] 2) Electrochemical performance characterization
[0159] ① Prepare test cells of each negative electrode composite material separately:
[0160] S1-S3, DS1, DS2, SC1-SC3, DSC1, DSC2, SCN1, SC1-2 to SC1-3, a conductive agent (specifically Super P) and a binder (specifically sodium carboxymethyl cellulose) were added to water at a mass ratio of 8:1:1, and stirred evenly to obtain a negative electrode slurry; each of the above negative electrode slurries was coated on a negative electrode collector (specifically copper foil), vacuum dried at 110°C for 12h, and then rolled and cut to obtain each negative electrode sheet;
[0161] In an argon-protected glove box, a metal lithium sheet is used as a counter electrode, and the negative electrode sheet, a diaphragm (specifically a commercial polyethylene diaphragm) and the above counter electrode are stacked in sequence, packaged and filled with electrolyte to obtain a 2032-type button cell, wherein the electrolyte is a 1 mol / L LiPF6 solution, and the electrolyte solvent is ethylene carbonate and diethyl carbonate in a volume ratio of 1:1.
[0162] ② The test batteries prepared as above were placed in an electrochemical test cabinet, and discharged at a constant current of 0.1C to 0.005V at 25°C, allowed to stand for 5 minutes, and then discharged at a constant current of 0.02C to 0.005V and allowed to stand for 5 minutes, and then charged to 1V at a constant current of 0.1C for cycle testing. The reversible capacity of the negative electrode composite material, the first coulombic efficiency, and the cycle capacity retention rate of the battery after 100 cycles were calculated. The results are summarized in Tables 2 to 5.
[0163] ③ At 25°C, test the initial thickness of each negative electrode sheet just prepared, then take the button cell prepared in step ①, charge it to 0.05V, make the negative electrode fully lithium-state, disassemble it, test the thickness of the negative electrode sheet, record the thickness increment of the negative electrode sheet, and calculate the expansion rate of the negative electrode sheet. Among them, the expansion rate of the negative electrode sheet = the thickness increment of the negative electrode sheet / the initial thickness of the negative electrode sheet × 100%, and the results are summarized in Tables 2 to 5 respectively.
[0164] Table 1
[0165] Case Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Carbon mass content >90% >90% >90% >90% >90% <![CDATA[Total pore volume (cm 3 / g)]]> 0.87 0.86 0.84 0.85 0.86 <![CDATA[Specific surface area (m 2 / g)]]> 1978 1940 1932 1945 1796 Volume proportion of micropores 91% 89% 87% 86% 74% Volume proportion of the first type of pores 57% 51% 50% 33% 38% Volume proportion of the second type of pores 34% 38% 37% 53% 36% Volume proportion of the third type of pores 99.5% 99.4% 99.3% 98.2% 90.2%
[0166] Table 2
[0167]
[0168] Table 3
[0169]
[0170] Table 4
[0171] Case SCN1 Silicon content 46% Particle size D50 (μm) 7.6 <![CDATA[Specific surface area (m 2 / g)]]> 2.8 Powder conductivity (S / cm) 2.5 True density(g / cc) 2.05 Reversible capacity (mAh / g) 1758 First coulombic efficiency 88.5% Capacity retention after 100 cycles 98% Expansion rate of negative electrode 61%
[0172] Table 5
[0173]
[0174] It can be seen from the data in Tables 1 and 2 that, when the total pore volume of the three-dimensional porous material is similar, the silicon content in the negative electrode composite materials S1-S3 prepared from the three-dimensional porous material provided in the embodiment of the present application is significantly higher than that in the comparative examples DS1-DS2, and the reversible capacity is significantly higher than that in the comparative examples DS1-DS2, indicating that the three-dimensional porous material in the embodiment of the present application has more effective deposition pores. At the same time, since the opening diameter of the openings in the three-dimensional porous material provided in the embodiment of the present application is more evenly distributed, the final negative electrode composite material can also exhibit low expansion characteristics and good cycle performance while having a high reversible capacity.
[0175] Combining the data in Tables 2 and 3, it can be found that carbon coating can greatly improve the electronic conductivity of the negative electrode composite material, improve the cycle performance, and further reduce the expansion rate of the negative electrode composite material, while also slightly increasing the reversible capacity. At the same time, the specific surface area of the negative electrode composite material decreases significantly after carbon coating, indicating that the carbon coating layer is also formed in the open pores of the three-dimensional porous material.
[0176] Furthermore, combining the data in Tables 3 and 4, it can be seen that N doping further improves the electronic conductivity and reversible capacity of the negative electrode composite material, and further optimizes the cycle performance, indicating that its doping can also improve the stability of the negative electrode composite material.
[0177] It is not difficult to see from the data in Table 5 that by adjusting the silicon content in the negative electrode composite material, the change trends of the cycle performance and the reversible capacity are opposite, and the change trends of the cycle performance and the negative electrode expansion rate are opposite. Ordinary technicians in this field can flexibly adjust the silicon content (that is, the content of nanoparticles) in the negative electrode composite material according to actual needs.
[0178] The above is an exemplary embodiment of the present application. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made thereto without departing from the principles of the present application. These improvements and modifications are also considered to be within the scope of protection of the present application.
Claims
1. A three-dimensional porous material, characterized in that: The three-dimensional porous material includes a plurality of openings. Based on the total opening volume of the three-dimensional porous material, the volume of openings with an opening diameter ≤ 2 nm accounts for ≥ 70%, and the volume of openings with an opening diameter in the range of 1 nm-2 nm accounts for ≥ 50%.
2. The three-dimensional porous material according to claim 1, characterized in that: Based on the total open pore volume of the three-dimensional porous material, the volume of open pores with an opening diameter of ≤2 nm accounts for ≥85%.
3. The three-dimensional porous material according to claim 1 or 2, characterized in that: Based on the total open pore volume of the three-dimensional porous material, the volume of open pores with an opening diameter of less than 1 nm accounts for ≤40%.
4. The three-dimensional porous material according to claim 3, characterized in that: Based on the total open pore volume of the three-dimensional porous material, the volume proportion of open pores with an opening diameter of less than 1 nm is ≤38%.
5. The three-dimensional porous material according to any one of claims 1 to 4, characterized in that: Based on the total open pore volume of the three-dimensional porous material, the volume of open pores with an opening diameter of >5 nm accounts for <1%.
6. The three-dimensional porous material according to any one of claims 1 to 5, characterized in that: The total pore volume of the three-dimensional porous material is greater than 0.5 cm 3 / g.
7. The three-dimensional porous material according to any one of claims 1 to 6, characterized in that: The material of the three-dimensional porous material includes at least one of conductive carbon, conductive ceramic or metal.
8. A negative electrode composite material, characterized in that: The negative electrode composite material comprises the three-dimensional porous material according to any one of claims 1 to 7 and a plurality of nanoparticles located in the open pores; The material of the nanoparticles includes at least one of a silicon-containing material, a phosphorus-containing material or a tin-containing material.
9. The negative electrode composite material according to claim 8, characterized in that: The size of the nanoparticles in at least one direction is ≤2 nm.
10. The negative electrode composite material according to any one of claims 8 to 9, characterized in that: The negative electrode composite material further includes a coating layer formed on the surface of the three-dimensional porous material; The coating layer comprises a carbon coating layer and / or a fast ion conductor coating layer, or a composite coating layer; wherein the material of the composite coating layer comprises a carbon material and a fast ion conductor material; The thickness of the coating layer is ≤20nm.
11. The negative electrode composite material according to claim 10, characterized in that: The carbon coating layer is also formed in the open pores of the three-dimensional porous material.
12. The negative electrode composite material according to any one of claims 8 to 11, characterized in that: The negative electrode composite material contains a doping element; the doping element is at least one of N, P or S.
13. The negative electrode composite material according to claim 12, characterized in that: The nanoparticles contain the doping element.
14. The negative electrode composite material according to claim 12 or 13, characterized in that: The three-dimensional porous material contains the doping element.
15. The negative electrode composite material according to any one of claims 12 to 14, characterized in that: The mass proportion of the doping element in the negative electrode composite material is less than 10%.
16. The negative electrode composite material according to any one of claims 8 to 15, characterized in that: The mass of the plurality of nanoparticles accounts for 30%-80% of the total mass of the negative electrode composite material.
17. A negative electrode plate, characterized in that: It comprises a current collector and a negative electrode material layer arranged on the surface of the current collector, wherein the negative electrode material layer comprises the negative electrode composite material according to any one of claims 8 to 16.
18. A secondary battery, characterized in that: The secondary battery comprises the negative electrode sheet and the positive electrode sheet as claimed in claim 17, and an electrolyte located between the negative electrode sheet and the positive electrode sheet.
19. An electrical equipment, characterized in that: The electric device comprises the secondary battery as claimed in claim 18.
20. An energy storage system, characterized in that: The energy storage system comprises the secondary battery as claimed in claim 18.
Citation Information
Cited By
Three-dimensional porous material, negative electrode composite material and use
EP4787467A1
Three-dimensional porous material, negative electrode composite material and use
WO2025066502A1